Peranan organisasi pembelajaran dalam mengoptimalkan inovasi guru - Widodo Widodo (Pusat Kajian Bimbingan dan Konseling FIPPS Unindra, 2018)
Inovation is the teacher's behavior aimed to produce, introduce or apply new findings in the form of ideas and solutions that benefit the organization, which is sourced fromexploration opportunities, generativity, informati investigation, fighting, and applications. The lack of innovation among teachers is not without cause. One of the most important is learning organization. This research was conducted to analyze the role of learning organization in optimizing teacher innovation. The research used qualitative approach with descriptive method. Data obtained through literature review and analyzed descriptively-qualitative. The results showed that teacher innovation is needed in the learning process so that schools need to optimize teacher innovation through the revitalization of learning organization.